The Reality of Teachers’ Use of Modern Technology in Serving the Educational Process from the Point of View of School Managers A Field Study in the Schools of Second Cycle of Basic Education in Lattakia City - حبيب, ليث; خضر علي; ثناء غانم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to know the degree of teachers’ use of modern technology in serving the educational process from the point of view of the managers of basic education schools in Lattakia City, and to know the differences in the degree of teachers’ use of modern technology in serving the educational process from the point of view of the managers according to the variables (number of years of experience, and training courses in technology field). The researcher used the descriptive approach, and the tool was a questionnaire, which was applied to a sample of (40) managers in the schools of the second cycle of basic education in Lattakia City. The results research showed that the evaluation of the research sample members of the school managers of the second cycle of basic education in the city of Lattakia to the degree of teachers' use of modern technology in the service of the educational process came to a medium degree. The results also showed that there were no statistically significant differences between the answers of the managers of the research sample members about the reality of teachers’ use of modern technology in the service of the educational process according to the variable years of experience, and the presence of statistically significant differences according to the variable of training courses, in favor of the managers who followed two training courses.